[18F]Ethenesulfonyl Fluoride as a Practical Radiofluoride Relay Reagent. Issue 32 (9th May 2019) - Zhang, Bo; Fraser, Benjamin H.; Klenner, Mitchell A.; Chen, Zhen; Liang, Steven H.; Massi, Massimiliano; Robinson, Andrea J.; Pascali, Giancarlo
Abstract: Fluorine‐18 is the most utilized radioisotope in positron emission tomography (PET), but the wide application of fluorine‐18 radiopharmaceuticals is hindered by its challenging labelling conditions. As such, many potentially important radiotracers remain underutilized. Herein, we describe the use of [ 18 F]ethenesulfonyl fluoride (ESF) as a novel radiofluoride relay reagent that allows radiofluorination reactions to be performed in minimally equipped satellite nuclear medicine centres. [ 18 F]ESF has a simple and reliable production route and can be stored on inert cartridges. The cartridges can then be shipped remotely and the trapped [ 18 F]ESF can be liberated by simple solvent elution. We have tested 18 radiolabelling precursors, inclusive of model and clinically used structures, and most precursors have demonstrated comparable radiofluorination efficiencies to those obtained using a conventionally dried [ 18 F]fluoride source. Abstract : At the ready : [ 18 F]Ethenesulfonyl fluoride ([ 18 F]ESF) can be trapped into inert cartridges and released to provide a ready‐to‐use labelling solution, reducing the radiochemistry equipment needed.